Исследование электрогидродинамических характеристик и тестирование алгоритмов оптимизации разрядноимпульсных технологий, использующих высоковольтный пробой в жидких средах - Вовченко, А.И.; Блащенко, А.Д.; Дивак, Н.П.; Тертилов, Р.В. (Технічна електродинаміка, 2011)
The statistical investigation of samples of pressure value in the volume point by spark discharge is made. The distribution law is defined. The correlation analysis of electrodynamical and hydrodynamical is performed. By comparison of calculative and experimental data, the usage of mathematical models and calculative algorithms applied for high voltage breakdown is justified in terms of optimization of electrohydropulse technologies.